Plant tolerance to high temperature in a changing environment: scientific fundamentals and production of heat stress-tolerant crops - Bita, Craita; Gerats, Tom (Frontiers in Plant Science, 2013)
Global warming is predicted to have a general negative effect on plant growth due to the negative effect of high temperatures on plant development. The increasing threat of climatological extremes, including very high temperatures might lead to catastrophic loss of crop productivity and result in wide spread famine. In this review we assess the impact of global climate change on the production of agricultural crop production. There is a differential effect of climate change both in terms of geographic location and the crops that have will be likely to show the most extreme reductions in yield as a result of warming in general and the expected fluctuations in temperature. High temperature stress has a wide range of effects on plants both in terms of physiology, biochemistry and gene regulation pathways. In this review we present the recent advances of research on all these level of investigation focusing on potential leads that may help to understand more fully the mechanisms that make plants tolerant or susceptible to heat stress. Finally we review possible mechanisms and methods which can lead to the generation of new varieties that will allow sustainable yield production in a world likely to be challenged both by increasing population, higher average temperatures and larger temperature fluctuations.